The impact of body vigilance on help-seeking for cancer 'alarm' symptoms: a community-based survey - Kelly Winstanley; Cristina Renzi; Claire Friedemann Smith; Jane Wardle; Katriina L. Whitaker (BMC, 2016)
Abstract Background The act of detecting bodily changes is a pre-requisite for subsequent responses to symptoms, such as seeking medical help. This is the first study to explore associations between self-reported body vigilance and help-seeking in a community sample currently experiencing cancer 'alarm' symptoms. Methods Using a cross-sectional study design, a 'health survey' was mailed through primary care practices to 4913 UK adults (age ≥50 years, no cancer diagnosis), asking about symptom experiences and medical help-seeking over the previous three months. Body vigilance, cancer worry and current illness were assessed with a small number of self-report items derived from existing measures. Results The response rate was 42% (N = 2042). Almost half the respondents (936/2042; 46%) experienced at least one cancer alarm symptom. Results from logistic regression analysis revealed that paying more attention to bodily changes was significantly associated with help-seeking for cancer symptoms (OR = 1.44; 1.06-1.97), after controlling for socio-demographics, current illness and cancer worry. Being more sensitive to bodily changes was not significantly associated with help-seeking. Conclusions Respondents who paid attention to their bodily changes were more likely to seek help for their symptoms. Although the use of a cross-sectional study design and the limited assessment of key variables preclude any firm conclusions, encouraging people to be body vigilant may contribute towards earlier cancer diagnosis. More needs to be understood about the impact this might have on cancer-related anxiety.